THE INFLUENCE OF HAJJ OFFICERS’ COMMUNICATION PSYCHOLOGY ON PILGRIMS’ SATISFACTION IN UMRAH SERVICE AT PT. DARUL ARQAM TRAVEL TOUR KRAKSAAN - Malikul Habsi (International Journal of Multidisciplinary Reseach, 2025)
This study analyzes how the communication psychology of Hajj officers influences pilgrims’ satisfaction in Umrah services at PT. Darul Arqam Travel Tour Kraksaan. The findings reveal that officers who demonstrate strong psychological communication skills such as empathy, emotional awareness, active listening, message clarity, and adaptive interaction significantly enhance pilgrims’ emotional comfort, trust, and overall satisfaction. Clear and structured information delivery reduces confusion during worship activities and travel procedures, especially for first-time pilgrims. Despite challenges such as diverse personalities, varying levels of understanding, and emotional fatigue among pilgrims, officers who apply adaptive communication strategies can effectively overcome these barriers and maintain a positive communication climate. The study concludes that psychological communication not only supports smooth service operations but also strengthens trust and long-term loyalty, making it an essential component in improving the quality of Umrah services.